Da fotograf Peter Elfelt “føjede billedet til historieskrivningen” - Wolthers, Louise (Fund og Forskning i Det Kongelige Biblioteks Samlinger, 2014)
NB: Artiklen er på dansk, kun resuméet er på engelsk. Louise Wolthers: When photographer Peter Elfelt “added the picture to the writing of history”. The Centre for Maps and Pictures of The Royal Library contains a large collection of photographs, accounting books and records from Peter Elfelt (1866-1931). Photographs from Elfelt & Co. was already marketed as “historic pictures” to their contemporaries and have frequently been used in later works, particularly popular history books. The article analyses a number of the sociocultural contexts, which the pictures have functioned in and illustrates which type of Danish history the photographs have mediated. Among other things, Elfelt’s work as a modern business man and his role as ‘auteur’ are included, while focusing on the use of his photographs in advertising for one of his major customers, clothing manufacturer Francis Zachariae. The photographs primarily show to have communicated and supported a national romantic and nostalgic view of history, which has gained authority due to the apparent objectivity of the photograph. In the article, more principal questions on the role of photographs in historiography are touched upon. Official and private picture collections contain extensive photographic material from the previous century which may contribute to a historic knowledge which cannot be gained through written sources. But why are photographs then solely used in the historic field as passive illustrations? Which challenges do they represent to the critical methodology and how can we even address the historical photograph?